Mineral Commodity Summaries 1984 - An Up-To-Date Summary Of 87 Nonfuel Mineral Commodities ? Aluminum (The National Institute for Occupational Safety and Health (NIOSH), 1984)
1. Domestic Production and Use: In 1983, 12 companies operated 27 primary aluminum reduction plants, with 4 firms accounting for 65% of production. Washington, Oregon, and Montana accounted for 35% of the production; Indiana, Kentucky, Maryland, New York, Ohio, and West Virginia 35%; Tennessee, Alabama, South Carolina, and North Carolina 14%; other central States 16%. Based on published producer prices, output of primary metal in 1983 was valued at over $5.7 billion. Aluminum consumption by 25,000 firms was centered in the East Central United States. Packaging accounted for an estimated 37% of domestic consumption in 1983, transportation 19%, building 17%, electrical 9%, consumer durables 8%, and other uses 10%.